A study of linguistic features of the expressions relating to kim, mộc, thủy, hỏa, thổ in truyen kieu by nguyen du and in its english translational equivalents by michael counsell - Ngô,Thị Phụng; Phan Văn Hòa (ĐHĐN : ĐHĐN., 2015)
The thesis is conducted to study linguistic features of the expressions relating to Kim, Mộc, Thủy, Hỏa, Thổ in Truyen Kieu by Nguyen Du and in Its English Translational Equivalents by Michael Counsell”. The aim of the study is to find out similarities and differences of the expressions relating to Kim, Mộc, Thủy, Hỏa, Thổ in English and Vietnamese. Two main methods will be used in this study are descriptive and contrastive methods in both Vietnamese and English versions. By quantitative and qualitative analyzing 387 samples under study are words, phrases containing the expressions relating to Kim, Mộc, Thủy, Hỏa, Thổ in Truyen Kieu by Nguyen Du and the translational version. With the theoretical background, the structural features of these devices in Truyen Kieu and its translational version are identified and described with in-depth analysis of linguistic features. Moreover, the study also suggests some implications in learning a foreign language or translating a literary word as well as for further studies put forward. Through this study, there is an inseparable relationship between linguistics and fantastic literature to the large extend; stylistics and literature to the small extend. Furthermore, it also provides the teachers and learners with some useful techniques.
Keywords: linguistic features of the expressions relating to kim, mộc, thủy, hỏa, thổ in truyen kieu by nguyen du and in its english translational equivalents by michael counsell; linguistic features -- expressions relating to kim, mộc, thủy, hỏa, thổ -- english translational equivalents